IMPROVING THE BALANCE MOVEMENT OF LOWER-GRADE STUDENTS THROUGH THE MODIFICATION OF ENGKLEK TRADITIONAL GAMES - Masnur Ali; Qory Jumrotul Aqobah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
This research aims to improve the balancing movement of lower-grade students through the modification of traditional games called engklek in SDN Delingseng, Cilegon City, Banten Province. The object of the research was 32 students of grade 1 students at SDN Delingseng. This research is an action research consisting of two cycles. Modification of the engklek game is made by modifying the rules, the field, and the game that in accordance with the stages of children’s motion learning and used in accordance with existing communities in the Cilegon city itself. The instrument of this research is a test to measure static balancing namely standing stork test that is adjusted to the age criteria for grade 1 students (6-8 years). The results showed an improvement in the first and second cycles of both male and female students with the percentage of male students, 2 students in the poor category (11.11%), 5 students in the moderate category (27.78%) and 11 students in the good category (61.11 %). While the female students obtained the result of 2 students in the poor category (14.29%), 4 students in the moderate category (28.57%) and 8 students in the good category (57.14%). Based on the results of the research showed that the application of the engklek traditional game modifications can improve the balance movement in the low-grade students. Keyword: Balance; Engklek Game; Traditional Games